Report of one case with de novo mutation in TLK2 and literature review - Han-Yue Li; Chun-Ming Jiang; Ruo-Yan Liu; Chao-Chun Zou (BMC, 2024)
Abstract TLK2 variants were identified as the cause for several neurodevelopmental disorders by impacting brain development. The incidence of mutation in TLK2 is low, which has common clinical features with other rare diseases. Herein, we reported a 5-year-old boy with TLK2 heterozygous mutation who presented distinctive facial features, gastrointestinal diseases, short stature, language delay, autism spectrum disorder, heart diseases, abnormal genitourinary system and skeletal abnormality. Moreover, we reviewed previous reported patients and our case in order to investigate more information on genotype-phenotype correlation and identify significant clinical characteristics for better diagnosis.